Enhancement of laser absorptivity in metal by laser surface modification - Amira Qistina Syamimi, Zaifuddin; Aiman, Mohd Halil; Quazi, Moinuddin Mohammed; Muhammad Izhar, Ishak (2021)
An innovation which currently in 4th TRL aims to improve laser-material interaction by increasing absorption of laser energy through surface roughness using laser surface modification